2015
DOI: 10.14814/phy2.12519
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin receptors V1aand V2 are not osmosensors

Abstract: Herein, we investigated whether G protein-coupled signaling via the vasopressin receptors of the V1a and V2 subtypes (V1aR and V2R) could be obtained as a direct response to hyperosmolar challenges and/or whether hyperosmolar challenges could augment classical vasopressin-dependent V1aR signaling. The V1aR-dependent response was monitored indirectly via its effects on aquaporin 4 (AQP4) when heterologously expressed in Xenopus oocytes and V1aR and V2R function was directly monitored following heterologous expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Biological activity of the vasopressin was therefore verified in V 1a R-expressing COS-7 cells in a parallel experimental series, which illustrated V 1a Rdependent down-regulation of AQP4 in V 1a R/AQP4expressing oocytes. 44 Ca 2þ imaging revealed lack of V 1a R activity in the primary cultures of bovine cerebral endothelium, which aligns well with low levels of V 1a R transcript in cerebral endothelium 12,25 and lack of V 1a R expression in capillary endothelial membrane as determined by immunohistochemistry and autoradiography. 26,52 Although we are unaware of the experimental explanation to the diversion from the report by O'Donnell et al 27 in which V 1a R-mediated NKCC1 activation was demonstrated, 27 a partial reason may be exposure of the co-culture to the glucocorticoid dexamethasone in order to induce BBB properties: 30 Dexamethasone exposure may abolish the vasopressin-dependent stimulation of NKCC1 activity.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Biological activity of the vasopressin was therefore verified in V 1a R-expressing COS-7 cells in a parallel experimental series, which illustrated V 1a Rdependent down-regulation of AQP4 in V 1a R/AQP4expressing oocytes. 44 Ca 2þ imaging revealed lack of V 1a R activity in the primary cultures of bovine cerebral endothelium, which aligns well with low levels of V 1a R transcript in cerebral endothelium 12,25 and lack of V 1a R expression in capillary endothelial membrane as determined by immunohistochemistry and autoradiography. 26,52 Although we are unaware of the experimental explanation to the diversion from the report by O'Donnell et al 27 in which V 1a R-mediated NKCC1 activation was demonstrated, 27 a partial reason may be exposure of the co-culture to the glucocorticoid dexamethasone in order to induce BBB properties: 30 Dexamethasone exposure may abolish the vasopressin-dependent stimulation of NKCC1 activity.…”
Section: Discussionsupporting
confidence: 74%
“…(g) Ca 2+ response as a function of time determined in primary cultured endothelial monocultures loaded with Fura2-AM and treated with vasopressin (1 µM), ATP (100 µM), or control buffer. (h) Dose-dependent stimulation of IP 1 response by vasopressin in hV 1a R-transfected COS7 cells (figure adapted from Lykke et al., 44 n = 7). (i) Vasopressin-mediated stimulation of NKCC1 activity in hV 1a R/rNKCC1-expressing oocytes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because mistrafficked mutants do not reach their biological site of action (so coupling cannot be assessed) and the use of pharmacoperones is a relatively new approach in drug discovery, there is little information regarding the characteristics of rescued mutants, such as whether they exhibit constitutive activity or second messenger bias. The WT V2R predominantly signals through coupling to Gs, however, it has been shown to couple to Gq by activating phospholipase C [ 15 , 16 ]. There are several V2R mutants that are retained in the ER, including the L83Q V2R mutant.…”
Section: Introductionmentioning
confidence: 99%